Different mechanosensory stimulations of the lower back elicit specific changes in hemodynamics and oxygenation in cortical sensorimotor areas—A fNIRS study - Vrana, Andrea (Brain Behav, 2016)
BACKGROUND AND OBJECTIVES: This study aimed at investigating the feasibility of functional near‐infrared spectroscopy (fNIRS) to measure changes in cerebral hemodynamics and oxygenation evoked by painful and nonpainful mechanosensory stimulation on the lower back. The main objectives were to investigate whether cortical activity can be (1) detected using functional fNIRS, and (2) if it is possible to distinguish between painful and nonpainful pressure as well as a tactile brushing stimulus based on relative changes in oxy‐ and deoxyhemoglobin ([O(2)Hb] and [HHb]). METHODS: Twenty right‐handed subjects (33.5 ± 10.7 years; range 20–61 years; 8 women) participated in the study. Painful and nonpainful pressure stimulation was exerted with a thumb grip perpendicularly to the spinous process of the lumbar spine. Tactile stimulation was realized by a one‐finger brushing. The supplementary motor area (SMA) and primary somatosensory cortex (S1) were measured bilaterally using a multichannel continuous‐wave fNIRS imaging system. RESULTS: Characteristic relative changes in [O(2)Hb] in the SMA and S1 after both pressure stimulations (corrected for multiple comparison) were observed. [HHb] showed only much weaker changes (uncorrected). The brushing stimulus did not reveal any significant changes in [O(2)Hb] or [HHb]. CONCLUSION: The results indicate that fNIRS is sensitive enough to detect varying hemodynamic responses to different types of mechanosensory stimulation. The acquired data will serve as a foundation for further investigations in patients with chronic lower back pain. The future aim is to disentangle possible maladaptive neuroplastic changes in sensorimotor areas during painful and nonpainful lower back stimulations based on fNIRS neuroimaging.